Sceptical Paths Enquiry and Doubt from Antiquity to the Present - Haliva, Racheli; Schmid, Stephan; Spinelli, Emidio; Veltri, Giuseppe (Studies and Texts in Scepticism, 2019)
Sceptical Paths gathers a variety of innovative studies that inquire into the presence and function of sceptical elements, strategies, and approaches in various traditions throughout Ancient, Medieval, Modern, and contemporary philosophy. Special attention is given to the place of sceptical argumentation in religious authors, challenging commonly held distinctions within the historiography of scepticism, and introduction of lesser-known thinkers.